Performance Test with TiO2 Modified Activated Carbon on Pilot Scale Phenol Removal - Slamet Slamet; Ade Putera; Setijo Bismo (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2008)
The integrated of activated carbon adsorbent and TiO2 photocatalyst (TiO2/AC) has been synthesized and evaluated to remove phenol in the continuous pilot scale system. TiO2/AC was prepared by mixing of AC into sol system consisting of TiO2 Degussa P-25, water, and tetraehtyl orthosilicate (TEOS) solution as a source of silica. The mixtures then evaporated at ±97oC and calcined at 400oC. Performance test of the material was conducted using Tubular-V-Collector (TVC) reactor that equipped with 14 UV black light lamps. The experimental results show that the phenol could effectively be removed through simultaneous adsorption and photocatalysis. Within the residence time of 6 minutes, TiO2/AC could continuously remove the 50 ppm of phenol by 100% phenol removal as long as 5 hours.